Determinants of Investment Interest Among Management Students, Case Study: Students of Universitas Pembangunan Nasional Veteran Jawa Timur - Firdaus, Andrew Baihaqi; Wikartika, Ira (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Investment involves the long-term allocation of funds with the objective of generating profits. Notably, the number of investors has experienced a significant increase over the years. This phenomenon can be attributed to several factors that positively influence the growth of future investment users, thereby motivating the investment interest of potential investors to allocate their capital in the Indonesian capital market. This research aims to analyze investment interest by examining the influence of financial literacy, financial self-efficacy, risk perception, and return perception on investment interest among Management students of UPN